Shear Strength of Eucalyptus saligna Wood Joints Bonded with Polyvinyl Acetate Adhesive - Biazzon, Joao C. [UNESP]; Lima Jr, Mauri P. [UNESP]; Munis, Rafaele A. [UNESP]; De Araujo, Victor A.; Morales, Elen A. M. [UNESP]; Goncalves, Marcos T. T. [UNESP]; Bueno, Marcus A. P. [UNESP]; Moizes, Fabio A. [UNESP]; Leite, Sueli S. [UNESP]; Salvadeo, Vitor M. [UNESP]; Archangelo, Andreia [UNESP]; Nasser, Silvia M. [UNESP]; et al. (North Carolina State Univ Dept Wood & Paper Sci, 2019)
Reforestation wood is interesting for construction, due to its potential as material source for manufacturing. For this purpose, the Eucalyptus genus has resulted in a better characterization of the material properties. During the production process, wood is machined at some stage, which influences the wood gluing quality. This study considered the performance of Eucalyptus saligna wood joints bonded with four commercial polyvinyl-acetate-based resins with different physical characteristics and chemical compositions. The surfaces of samples were prepared and machined by an up-milling process, using a planer, with wood feed rates of 6 m/min, 11 m/min, 16 m/min, and 21 m/min, which had advances per tooth of 0.25 mm, 0.45 mm, 0.66 mm, and 0.87 mm, respectively. The samples were prepared for shear strength testing of the glue line. During the preparation, all pieces were randomly bonded with regards to the formation plans of wood growth rings. Shear strength values were statistically compared to analysis of variance and Tukey test. Only C4 adhesive reached good results at all feed rates as well as having the best shear strength compared to other resins. Commercial adhesives had distinct interactions on the adhesive-wood interface, which resulted in different adhesion strengths.
Keywords: Eucalyptus saligna; Timber; Machining; Feed rate; Adhesion; Shear strength